Changes in Cardiovascular system among smokeless tobacco users attending tertiary care hospital in Andhra Pradesh, India - Dr. B Annaji; Dr. P Sreedevi; Dr. K Sudheer (International Journal of Medical Research and Review, 2020)
Background: Tobacco can be consumed as cigarettes and also as smokeless tobacco. Smokeless tobacco is a harmful tobacco product that contains over 3,000 chemicals, 7 including 28 known carcinogens (cancer-causing agents). Various forms of smokeless tobacco (mainly snuff and chewing tobacco) cause an immediate increase in heart rate and blood pressure. However, the relationship between smokeless tobacco uses on blood pressure remains unknown, especially in tertiary level hospitals. Our aim is to find out the smokeless tobacco use influence on cardiovascular parameters, for instance, pulse rate and blood pressure.Methods: This cross-sectional study was carried out to assess cardiovascular changes among adult male smokeless tobacco (ST) users. For this purpose, 50 male respondents were selected. The participants were selected from the medicine outpatient department of Great Eastern Medical School and Hospital, Srikakulam, Andhra Pradesh. Pulse rate and blood pressure were measured and ST uses behavior was assessed using self-reports. Statistical analysis was done by SPSS20.Results: In this study, the mean (±SD) of pulse rate was 83.2±12.3 beats/min. The mean (±SD) of systolic blood pressure was 158.72±24.84 mm of Hg and the mean (±SD) of diastolic blood pressure was 98.78±9.87 mm of Hg in smokeless tobacco users.Conclusion: Mean systolic and diastolic blood pressures were higher in smokeless tobacco users in the tertiary level hospital. However, the mean pulse rate was within the normal range.